PENDEKATAN RAPID RURAL APPRAISAL (RRA) DALAM MENGIDENTIFIKASI POTENSI DAN MASALAH ASPEK SOSIAL-BUDAYA MASYARAKAT KAMPUNG TELUK BAYUR: PENDEKATAN RAPID RURAL APPRAISAL (RRA) DALAM MENGIDENTIFIKASI POTENSI DAN MASALAH ASPEK SOSIAL-BUDAYA MASYARAKAT KAMPUNG TELUK BAYUR - Wahyu Widiantoro (ECO-BUILD, 2025)
This research aims to assess issues related to the condition of social and cultural aspects of the community in Teluk Bayur Village. The data collection method was conducted by Rapid Rural Appraisal (RRA) and analyzed by SWOT. The social approach uses Focus Group Discussion (FGD) by jointly identifying the potential and problems of the village.. It can be concluded that the large number of people of productive age creates opportunities in developing the agricultural sector. Complete educational facilities are sufficient in fulfilling the quality of education so that it can support human resources. Adequate assistance and media are needed for the community in managing existing potential, so that they can be facilitated in carrying out all activities related to utilization that bring positive and constructive aspects to the village.